Punishment of Child Perpetrators in the Crime of Sexual Intercourse - Helen Tessalonika Yoci; Echwan Iriyanto; Sapti Prihatmini (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
As time goes by, children who do not grow and develop like children in general have the potential to commit criminal acts, such as sexual intercourse. In this decision, the public prosecutor has charged 3 (three) articles in Law Number 17 of 2016 concerning the Stipulation of Government Regulations in place of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection with alternative forms. However, the alternative indictment raises questions regarding the accuracy in drafting the articles used, because if the judge cannot prove the child defendant's actions, then he could be released from inaccurate indictment articles. In addition, the child defendant in this decision was sentenced to a crime that was far from the maximum provisions stated in the article on the proven indictment. The judge's actions were deemed to have deviated from the laws and regulations used, namely Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, created legal uncertainty, and reduced the public's sense of distrust towards Law Enforcement Officials.